THE FRENCH MODEL FOR ASSESSING THE QUALITY OF HIGHER EDUCATION: CURRENT TRENDS - Batechko Nina; Durdas Alla (Borys Grinchenko Kyiv Metropolitan University, 2020)
The article deals with the current state of development of higher education in the French Republic. The higher educa-tion quality in France in the light of the European tendencies has been highlighted; the French model for assessing the quality of higher education has been analysed. The concept of higher education quality has been stated; the structure of France's higher education has been provided. The effectiveness, innovation and productivity which are expected from higher education in Europe today, have been emphasized. The significance of the continuing assessment in the French education system has been stressed. The historical background for the development of the French model for assessing the quality of higher education has been considered. The bodies participating in evaluating higher education in France have been analysed, and their roles and tasks have been stated. The possibility of the use of the positive French experience in higher education quality evaluation in Ukraine has been stated.